Diversité Et Structure Floristiques Sous Des Peuplements d’Acacias Australiens En Zone Forestière De La Côte d’Ivoire - Richard, Kouadio Kouassi; Adama, Bakayoko; Anatole, N’guessan Kanga; Djezou, Konan (European Scientific Journal, ESJ, 2016)
Since thirty years, four Australian Acacias species are introduced and studied in AnguÃ©dÃ©dou Research station. The station research is located in evergreen forest in the south of CÃ´te d’Ivoire. The objective of the introduction of these species, is to rehabilitate degraded grounds and fallow after growing. The study aims at appreciating the impact of Acacia species on floristic diversity and the regeneration of forest species. For collecting data, we use quadrat method (35 x 50 m and 6 x 6 m).This method permitted the inventory of 212 species on 1.05 ha. Among these species, 1.89 % are Ivorian endemic species and 11.32 % are endemic of West African flora. The flora under the different species of Acacia are relatively diversified and dense. The majority of plant inventoried under Acacia species have small diameters. The highest specific richness average per plots (36 m2) were noted in the 11 years old parcels of Acacia mangium (26.20Â±2.34) and 27 years old parcels of Acacia auriculaeformis (25.40Â±2.34) and Acacia crassicarpa (30.60Â±2.34). The mean values of diameters (dbh â‰¥ 2.5 cm) fluctuate from 2.94Â±0.56 cm for the 8 years old stands of Acacia mangium to 8.09Â±0.56 cm for the 27 years old settlements of Acacia crassicarpa. The results show that leguminous trees can be used for recolonization of the deforested areas in order to rebuild quickly their plant biodiversity.